Evaluation of Fresh and Frozen Beef Strip Loins of Equal Aging Periods for Palatability Traits - Ashton L McGinn; Ellie G Kidwell; Erin Beyer; Jessie Vipham; Lindsey K Decker; Michael Chao; Morgan Zumbaugh; Travis G. O'Quinn (Meat and Muscle Biology, 2024)
Although studies evaluating freezing are prevalent, most have used varied postmortem aging times to facilitate study design. The lack of a comprehensive study evaluating equally aged fresh and frozen steaks prevents a true under-standing of the impact of freezing. Therefore, the objective of this study was to determine the eating quality and consumer perception differences between fresh and frozen beef steaks of 3 equal aging periods. Beef carcasses were selected from a processing plant on 2 kill dates 1 wk apart to allow for a 1-wk freezing period, fabricated, and aged for 21, 28, or 35 d. On the same day, all samples of equal aging periods were fed to consumer and trained sensory panelists, sheared for shear force, and powdered for lab assays. For consumer panels, the first 4 steaks were given with no additional information, whereas the last 4 steaks were served with the labels “previously frozen” or “fresh, never frozen.” The consumer panelists rated the frozen samples as more tender (P<0.05) than the fresh samples but found no other differences (P>0.05). Even when given additional information, the perception of quality was not impacted (P>0.05). Similarly, the trained panelists rated the frozen samples higher (P<0.05) than the fresh counterparts for overall tenderness, but the fresh samples scored higher (P<0.05) for initial and sustained juiciness. Supporting the sensory data, the frozen steaks had lower (P<0.05) shear force values regardless of the aging period. However, the fresh samples resulted in lower (P<0.05) purge and cook loss. Although some meat quality factors were impacted by freezing, the overall eating quality and perception of quality were not negatively impacted. Therefore, frozen meat should not be discounted due to the eating quality or perception of the quality of beef steaks.